1971
DOI: 10.1071/ar9710809
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian response to gonadotrophin by Merino ewes selected for fecundity

Abstract: Medium-wool Merino ewes, from groups that, as a result of selection since 1954 for this character, have a low (O group) and high (T group) incidence of multiple births, were injected with 0,375,750, or 1500 i.u. pregnant mare serum gonadotrophin (PMSG) on day 13 or 15 of the oestrous cycle (day 1 is the day of oestrus). The two groups were compared on the basis of the occurrence of oestrus, number of ovulations, ovarian follicle score, plasma progesterone level, and weight of luteal tissue. Conception rate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 0 publications
8
18
0
Order By: Relevance
“…Cahill et al (1979) also showed a significant deviation between the two breeds in the number of growing follicles. This result explains the observations of Bindon, Ch'ang & Turner (1971), Smith (1976) and A. Lahlou-Kassi & J. C. Mariana (unpublished data) concerning the positive correlation between the prolificacy of a breed of ewe and its response in terms of numbers of ovulations to PMSG. Monniaux, Chupin & Saumande (1983) showed a positive correlation between the number of growing follicles in the ovary at the time of treatment and the number of luteinized follicles and the number of ovulations induced by an injection of 1200 i.u.…”
Section: Discussionsupporting
confidence: 80%
“…Cahill et al (1979) also showed a significant deviation between the two breeds in the number of growing follicles. This result explains the observations of Bindon, Ch'ang & Turner (1971), Smith (1976) and A. Lahlou-Kassi & J. C. Mariana (unpublished data) concerning the positive correlation between the prolificacy of a breed of ewe and its response in terms of numbers of ovulations to PMSG. Monniaux, Chupin & Saumande (1983) showed a positive correlation between the number of growing follicles in the ovary at the time of treatment and the number of luteinized follicles and the number of ovulations induced by an injection of 1200 i.u.…”
Section: Discussionsupporting
confidence: 80%
“…M. Bindon, M. A. Hillard & T. O'Shea, unpublished results), are similar to those seen in ewes with increased ovulation rate as a result of treatment with PMSG (Bindon, Ch'ang & Turner, 1971). …”
Section: Detection Ofantibodyformationsupporting
confidence: 65%
“…A similar relationship has been noted after PMSG stimulation for progesterone levels in ovarian vein blood (Short 1960) and peripheral plasma (Thorburn et aI. 1969;Bindon et al 1971). Ewes with two corpora lute a had greater blood progesterone levels than uniovular sheep (P < 0.01).…”
Section: Discussionsupporting
confidence: 52%